Measurement of W+W- production in pp collisions at root s=7 TeV with the ATLAS detector and limits on anomalous WWZ and WW gamma couplings - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
This paper presents a measurement of the W+W- production cross section in pp collisions at √s=7 TeV. The leptonic decay channels are analyzed using data corresponding to an integrated luminosity of 4.6 fb-1 collected with the ATLAS detector at the Large Hadron Collider. The W+W- production cross section σ(pp→W+W-+X) is measured to be 51.9±2.0(stat)±3.9(syst)±2.0(lumi) pb, compatible with the Standard Model prediction of 44.7-1.9+2.1 pb. A measurement of the normalized fiducial cross section as a function of the leading lepton transverse momentum is also presented. The reconstructed transverse momentum distribution of the leading lepton is used to extract limits on anomalous WWZ and WWγ couplings. © 2013 CERN.